2021
DOI: 10.7717/peerj.11406
|View full text |Cite
|
Sign up to set email alerts
|

Shiftwork, functional bowel symptoms, and the microbiome

Abstract: Background There are about 15 million Americans working full-time on evening, night, or rotating shifts. Between 48% and 81.9% of those working rotating or night shifts report abdominal pain, constipation, diarrhea and other symptoms of functional bowel disorders. The basis for this high prevalence of functional bowel disorders, including irritable bowel syndrome (IBS), among shift workers is unknown. Animal studies, however, suggest that circadian disruption, similar to that in shift workers, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Due to the following reasons, some articles were discarded: the study did not meet the inclusion criteria, the metadata provided by the study did not enable the differentiation of case and control samples, the accession number corresponding to the sequencing data of the study was not found in the repositories, and the quality of the sequences was too low for downstream analysis. After inclusion criteria evaluation, quality verification, and taxonomic assignment with DADA2, the total of analyzed studies were: five for CRC ( Lu et al., 2016 ; Clos-Garcia et al., 2020 ; Uchino et al., 2021 ; Du et al., 2022 ; Konishi et al., 2022 ), eight for CD ( Forbes et al., 2018 ; Zhou et al., 2018a ; Braun et al., 2019 ; Lloyd-Price et al., 2019 ; Weng et al., 2019 ; Alam et al., 2020 ; Bourgonje et al., 2022 ; Pisani et al., 2022 ), nine for UC ( Bajer et al., 2017 ; Halfvarson et al., 2017 ; Forbes et al., 2018 ; Zhou et al., 2018a ; Lloyd-Price et al., 2019 ; Weng et al., 2019 ; Alam et al., 2020 ; Quraishi et al., 2020 ; Bourgonje et al., 2022 ; Pisani et al., 2022 ), four for IBS ( Zhuang et al., 2018 ; Zhu et al., 2019 ; Wang et al., 2020 ; Rogers et al., 2021 ), and one for CDI Duan et al, (2020) . Additional information on the mentioned studies is described in Supplementary Data 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Due to the following reasons, some articles were discarded: the study did not meet the inclusion criteria, the metadata provided by the study did not enable the differentiation of case and control samples, the accession number corresponding to the sequencing data of the study was not found in the repositories, and the quality of the sequences was too low for downstream analysis. After inclusion criteria evaluation, quality verification, and taxonomic assignment with DADA2, the total of analyzed studies were: five for CRC ( Lu et al., 2016 ; Clos-Garcia et al., 2020 ; Uchino et al., 2021 ; Du et al., 2022 ; Konishi et al., 2022 ), eight for CD ( Forbes et al., 2018 ; Zhou et al., 2018a ; Braun et al., 2019 ; Lloyd-Price et al., 2019 ; Weng et al., 2019 ; Alam et al., 2020 ; Bourgonje et al., 2022 ; Pisani et al., 2022 ), nine for UC ( Bajer et al., 2017 ; Halfvarson et al., 2017 ; Forbes et al., 2018 ; Zhou et al., 2018a ; Lloyd-Price et al., 2019 ; Weng et al., 2019 ; Alam et al., 2020 ; Quraishi et al., 2020 ; Bourgonje et al., 2022 ; Pisani et al., 2022 ), four for IBS ( Zhuang et al., 2018 ; Zhu et al., 2019 ; Wang et al., 2020 ; Rogers et al., 2021 ), and one for CDI Duan et al, (2020) . Additional information on the mentioned studies is described in Supplementary Data 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, the definitions of shift work in the included literature were inconsistent. In the included literature, there were about day work and shift work, [26][27][28][29] night work and shift work, [30] and regular work and shift work. [31] Secondly, the diagnostic criteria for IBS and FD in the literature are not completely consistent.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of circadian rhythms increases the risk of developing many of the diseases we have already touched upon in this review, such as obesity, diabetes, neurodegeneration, and cardiovascular disease [ 166 ]. Recent studies have demonstrated that compared to day shift workers, night shift workers are more prone to obesity, impaired lipid metabolism, and gastrointestinal disorders, all of which we know are also linked to diet and the microbiome [ 167 , 168 ]. So far it is unclear whether shift work causes changes in the microbiome in humans, but there is evidence from mice that circadian disruption can cause dysbiosis [ 168 , 169 , 170 ].…”
Section: Microbiota Lipid Metabolism and Circadian Rhythmsmentioning
confidence: 99%
“…Recent studies have demonstrated that compared to day shift workers, night shift workers are more prone to obesity, impaired lipid metabolism, and gastrointestinal disorders, all of which we know are also linked to diet and the microbiome [ 167 , 168 ]. So far it is unclear whether shift work causes changes in the microbiome in humans, but there is evidence from mice that circadian disruption can cause dysbiosis [ 168 , 169 , 170 ].…”
Section: Microbiota Lipid Metabolism and Circadian Rhythmsmentioning
confidence: 99%